G49(P) Rcpch stroke in childhood guidelines: are these being followed?. (25th October 2020) - Collins-Sawaragi, YC; Walker, H; Sanperaiglesias, J; Byrne, S; Wraige, E; Lumsden, D; Tang, S
Abstract : Aims: We investigate if the RCPCH Stroke in Childhood Guidelines (2017) are being followed in paediatric patients presenting with a 'brain attack'. Methods: We retrospectively collected two cohorts of paediatric patients aged over 2 years old presenting with symptoms suggestive of stroke ('brain attack') over 6 months between March and August 2019. Cohort 1 were patients from a Tertiary Hospital A&E department that were identified through the Symphony electronic database. Cohort 2 were from patient referrals to the Tertiary Paediatric Neurology Department documented in the electronic database. Patient demographics, symptoms, NIHSS (National Institute of Health Stroke Scale), investigations, time to brain scan, thrombolysis and thrombectomy rates and final diagnosis were collected. Results: 33 patients in Cohort 1 and 32 patients in Cohort 2 had symptoms that met possible stroke diagnosis. Mean age of all patients were 8.9 years (36 male, 29 female). The top 3 presenting symptoms were focal seizures (20/65), speech disturbance (14/65) and headache (13/65). Only 6 patients had NIHSS calculated. Cranial imaging was performed within 1 hour of admission in only 1/33 in the A&E cohort and 2/32 in the external referral cohort. 9/65 patients had a diagnosis of stroke: 2 transient ischaemic attacks, 5 ischaemic strokes, 1 venous stroke and 1 haemorrhagic stroke. 28/65 patients had other diagnoses requiring urgent treatment such as seizure disorders and infection. In total 2 patients were evaluated for thrombolysis – 1 patient received thrombolysis under the care of the adult stroke team. 2 patients were referred for thrombectomy but none were suitable candidates (1 symptom resolution before thrombectomy, 1 high risk of complications due to anticoagulation post-operatively). Conclusion: RCPCH Stroke in Childhood Guidelines are not consistently being followed, particularly with regards to calculation of NIHSS and delays in obtaining brain imaging. If guidelines are not followed, paediatric stroke patients and windows of treatment with thrombolysis/thrombectomy may be missed. This highlights the importance of having a paediatric stroke pathway in place.